(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
This paper presents the relations of the State and the Catholic Church in Chile between 1946 and 1958. It highlights the establishment of the constitutional framework of the Charter of 1925 that allowed its development and the friendly ties of ecclesiastical and civil powers is highlighted. The three constitutional governments, two radicals and one independent of national unity, had a permanent attitude of respect and closeness to the religious institution and its members. Similarly bishops and clergy were affable with administrative authorities and those in other areas of the country. It has to be considered that the Metropolitan Archbishop of the Chilean capital has traditionally assumed the representation of the national Church for all cases where the religious institution is related to the State and the Chilean Society, irrespective of other prelates who also held singular contacts.